2018
DOI: 10.1097/brs.0000000000002352
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Endplate Defect as Initiating Factor in Intervertebral Disc Degeneration

Abstract: 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 32 publications
4
73
2
Order By: Relevance
“…Earlier studies have shown, that endplate changes and DDD are related. [20,8] In the present study, no relevant increase of DDD grade was seen during follow up.…”
Section: Discussioncontrasting
confidence: 57%
“…Earlier studies have shown, that endplate changes and DDD are related. [20,8] In the present study, no relevant increase of DDD grade was seen during follow up.…”
Section: Discussioncontrasting
confidence: 57%
“…We can appreciate the reduction in L5-S1 intervertebral disc hydration and the increased extent of Modic 1 changes at the level of both endplates at the same level [20]. The vertebral body endplates are indeed considered the most vulnerable structure functional spinal unit [21]. They have a bony component and a hyaline cartilaginous component.…”
Section: Discussionmentioning
confidence: 97%
“…Rostral and caudal endplates were coded using middle sagittal slices at each lumbar segment for all baseline, and follow-up MRI scans, with no prior clinical knowledge of clinical status, scan sequence or subject details. Rostral and caudal endplate scores were summed to generate a total endplate (TEP) score for each lumbar level (13). Inter-rater agreement for the coding of endplate defect was calculated…”
Section: Evaluation Of Endplate Defectmentioning
confidence: 99%
“…Vertebral endplate defect heritability 8 LDD had been scored using 4-point grading system. In the 4-point grading system disc signal, disc bulge, disc height loss and anterior osteophytes were coded 0-3 from the atlas, using the middle slice MR image, as described previously (2,13,14). Disc degeneration summary score was calculated by summing scores for the four traits at each of the five lumbar levels.…”
Section: Evaluation Of Disc Degenerationmentioning
confidence: 99%